The Use of Think, Pair And Share (TPS) Strategy in Teaching Reading Skill - Yanpitherszon Liunokas (Institut Agama Islam Negeri Palopo, 2019)
This research deals with the teaching reading through think pair share strategy (TPS) at the fourth semester students of English Education Department, Nusa Cendana University, Kupang, NTT. The population of this research is the Fourth Semester Students of English Education Department, Nusa Cendana University, Kupang, NTT. Reading test was the instrument of this research. Based on the findings and discussion, the researcher concludes that the use of think pair share strategy parallel writing technique is effective in developing students’ vocabulary in writing at the Fourth Semester Students of English Education Department, Nusa Cendana University, Kupang, NTT. It was proven by there was a significant difference between the students’ mean score of pretest and posttest. In pretest, the students’ mean score is 26 and the students’ score in posttest is 51. In addition, the result of statistical analysis for level of significance (p=0.05). The probability value was smaller than α (0.00<0.05). it indicated that there is significant differences between the result of pre-test and post-test after giving treatment in building students’ reading skill ng by applying think pair share strategy (TPS) to the fourth semester students of English Education Department, Nusa Cendana University, Kupang, NTT.